Evaluation of Nitric Oxide and Interleukin-17 in the Serum of Men During the Fast of Ramadan - Hamideh Mozafari; Mohammad Mehdi Eftekharian; Ghodratollah Roshanaei; Mohammad Reza Safari; Gholamreza Shafiee (Journal of Advanced Biomedical Sciences, 2020)
Background & Objective: Nitric oxide gas is important in regulating blood vessel dilation, and consequently, blood pressure. Nitric oxide is continuously produced by endothelial cells known as a compound that plays an important role in the cardiovascular system.  Also, Interleukin-17 (IL-17) is a pro-inflammatory cytokine that can mediate protective innate immunity to pathogens or contribute to the pathogenesis of inflammatory diseases. In the current study, the plasma levels of nitric oxide and serum level of IL-7 were assessed before and after Ramadan month in fasting people, aimed at the scientific investigation of the possible preventing effects of fasting for cardiovascular disease. Materials & Methods: The present study 61 fasting man (30-60 years old) were selected and blood samples were collected from each one day before and one day after Ramadan month. Serum levels of Nitric oxide and IL-17 were measured in two groups by ELIZA kits. Results: The results of this study shown the serum level of nitric oxide was significantly increased in individuals before and after Ramadan month (from 16.17 ± 1.15 mmol/L to 22.17 ± 1.46 mmol/L, respectively) (P<0.0001). Also, the results indicate that serum level of IL-17 was statistically different in two groups (from 58.25 ± 10.59 pg/ml to 15.98 ± 4.66 pg/ml, respectively) (P<0.0001). Conclusion: The results of this study showed that nitric oxide and IL-17 levels decreased during the Ramadan month and so it can be concluded the fasting of Ramadan may have positive effects on cardiovascular and immune factors of the body.